Taxonomic study of the freshwater shrimps genus Atyoida Randall, 1840 (Crustacea: Decapoda: Atyidae) in Polynesia with a revalidation of A. tahitensis Stimpson, 1860 - Lorang, Camille; de Mazancourt, Valentin; Marquet, Gérard; Keith, Philippe (Zootaxa, 2020)
Numerous specimens of Atyoida were collected in Polynesia during specific samplings led by the Muséum national d’Histoire naturelle (MNHN, Paris) from 1983 to 2017. In the context of an integrative taxonomy, all the Polynesian specimens were morphologically and genetically studied. The molecular study proved that the specimens were split in two different clades separated by 7% genetic distance (16S) and geographically structured that can be considered as two distinct species. In this article, A. tahitensis Stimpson, 1860 from Eastern Polynesia is re-validated as a distinct species from A. pilipes (Newport 1847) from Vanuatu to Marquesas archipelago. The morphological study, besides coloration patterns (Body blackish on its back, ornamented on its flanks with numerous bluish dots and longitudinal stripes for A. tahitensis; orange-yellow back as well as the antennular peduncle, telson and uropods with the flanks whitish ornamented with numerous blue-black patterns of various shapes for A. pilipes), did not allow us to find characters to distinguish easily the two species. Detailed re-descriptions and the geographical distribution of these two species are given and a neotype deposited in the MNHN (Paris) is designated for A. tahitensis.